PHYSICOCHEMICAL CHARACTERISTICS OF SURFACE WATER QUALITY OF PACHAMALAI HILLS, TAMILNADU. - PRABAKARAN P, SIVASUBRAMANIAN C (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Water is an essential component of the environment and it sustains life on the earth. Moving water dilutes and decomposes pollutants in an efficient manner than standing water, but many rivers and streams remain significantly polluted all around the world. The study was conducted to determine the surface water quality of Pachamalai Hills, TamilNadu. To perform the study surface water samples were collected from different locations and analyzed for various physicochemical parameters such as pH, Electrical Conductivity (EC), Total Dissolved Solids (TDS), Alkalinity, Total Hardness, Calcium (Ca), Magnesium (Mg), Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) and Nitrate. The analytical results of surface water quality parameters were compared with the World Health Organization (WHO) standards to assess their suitability for drinking purposes.